Implementation Situation of Information Technology at Local Governance of Nepal - Pandey, Romkant; Malla, Vijaya (Innovative Research Journal, 2023)
Implementation of broadband strategy, as well as information security basics, are important issues for local governments. Building a framework for ICT infrastructure development and offering e-services for businesses is making the local government a central body, influencing the development of the economy in the region. In this paper, we found that innovative technologies have not been used in service delivery at some local levels of Nepal. Some of the local levels were given the responsibility to the person who does not have any qualifications and knowledge related to information technology. The local government was not to be concerned about the security and sensitivity of the information technology-related equipment and materials used in the office and the capacity of the local level is weak in terms of expanding information technology infrastructures within their area and making necessary policy and legal arrangements for managing the use of information technology. This research focused on integrated software with a large capacity that needs to be developed and sent to all local levels through DoIT, needs to provide the technical knowledge and training for the IT manpower, every local level of Nepal has to develop and implemented its own Local Level IT Policy.